2018
DOI: 10.1097/md.0000000000013111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global spine balance and cervical regional alignment on determination of postoperative cervical alignment after laminoplasty

Abstract: The aim of this study is to analyze the combined impact of preoperative T1 slope (T1S) and C2-C7 sagittal vertical axis (C2-C7 SVA) on determination of cervical alignment after laminoplasty.Forty patients undergoing laminoplasty for cervical spondylotic myelopathy (CSM) with more than 2 years follow-up were enrolled. Three parameters, including cervical lordosis, T1S, and C2-C7 SVA, were measured by preoperative and postoperative radiographs. Receiver operating characteristics (ROC) curve analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
0
36
1
Order By: Relevance
“…In addition to age, the effect of preoperative T1S should be also considered to evaluate the radiological outcomes after laminoplasty between the CSM and OPLL groups. The preoperative high T1S is already known to be an important factor related to the development and deterioration of sagittal imbalance after laminoplasty [3,4]. In our study, T1S showed no signi cant differences between the two groups pre-and postoperatively.…”
Section: Discussioncontrasting
confidence: 45%
“…In addition to age, the effect of preoperative T1S should be also considered to evaluate the radiological outcomes after laminoplasty between the CSM and OPLL groups. The preoperative high T1S is already known to be an important factor related to the development and deterioration of sagittal imbalance after laminoplasty [3,4]. In our study, T1S showed no signi cant differences between the two groups pre-and postoperatively.…”
Section: Discussioncontrasting
confidence: 45%
“…A study conducted by Lin et al [ 19 ] have shown that T1 slope and C2–C7 SVA are goof predictors of LCL, in combination. They classified patients into four categories:…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have described various indices to predict LCL in patients undergoing laminoplasty. [ 18 19 20 21 ] The indices which may play an important role in predicting LCL are described in Table 1 and Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation of this study is that only cervical spinal radiographs were analyzed, as there were no data regarding the overall sagittal alignment of the spine. Although previous studies have reported that cervical curvature can be affected by overall spinal sagittal imbalance [16][17][18][19], only normal subjects with a normal cervical curvature were included in our present study, and we found no difference in OC4Ds as a function of changes in cervical curvature in neutral, flexion, and extension positions. However, we also recognize that cervical curvature changes can accelerate cervical degeneration, which may affect the results of OC4D measurements.…”
Section: Discussionmentioning
confidence: 51%